Cover, Redaksi, Daftar Isi JVet 17 (2) - I Wayan Batan (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2016)
Cover, Redaksi, Daftar Isi JVet 17 (2)